PEMBUATAN RADIO ONLINE DENGAN AUDIO STREAMING DAN VIRTUAL PRIVATE SERVER UNTUK KOMUNITAS BLOGER SEMARANG LOENPIA.NET - Suprayogi, Mohammad Sani (Jurnal Transformatika, 2012)
Information  technology,  especially in terms of  audio  processing  has been  greatly expanded,  with the  use of  Internet  and  webtechnologies  are  able to  deliver the  audio data  to the entire  world.  That  Audio  Streaming, a service that  can be used  by anyone  todisseminate  information. Conventional  radios  have limited  range  and  frequency of  broadcasts.  Utilizing  Audio  Streaming,  OnlineRadio  we  can  make  that can  be heard  from around the  world.  A device that  takes more  simple that anyone  can  create  and  take advantage of  this technology.This research  proves  that by using  VPS,  Linux,  Internet,  and  Website.  Anyone  can  make  OnlineRadio  easily and  used for  any purpose.
Keywords: audio streaming; radio online; vps; linux; website